Informe final de la pasantía en la empresa Petrocol Services SAS en el área de Servicios (2023)
Petrocol Services S.A.S, is a huilense company dedicated to providing efficient solutions to the industrial sector. This company has highly qualified operational personnel that fulfills the legal obligations and agreements agreed in the different areas of the country. This company has established as strategic objectives, to achieve a point of balance in the delivery of its services because of the economic crisis that it lived; incorporate the different solutions into the environmental line structure; importing efficient equipment; have the capacity to sell, install, maintain and sustain clean energy generation projects and carry out projects in South American countries. Based on this information, an analysis of internal and external factors will be carried out in order to find the current strengths, weaknesses, opportunities and threats of the company so that it can expand its horizons of economic growth in the market. To perform such analysis, an observation guide and DOFA matrix will be used as study tools to identify and establish an updated company diagnosis, which will allow to design an improvement strategy that will become the main pillar of the company, so that in the future this may be the best option in Colombia in terms of energy production because it has a model of cost efficiency, reliability, strategy and sustainability